2022
DOI: 10.3390/ijms23179726
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Gene Expression Profiling of the Peanut Small Seed Mutant Identified Genes Involved in Seed Size Control

Abstract: Seed size is a key factor affecting crop yield and a major agronomic trait concerned in peanut (Arachis hypogaea L.) breeding. However, little is known about the regulation mechanism of peanut seed size. In the present study, a peanut small seed mutant1 (ssm1) was identified through irradiating peanut cultivar Luhua11 (LH11) using 60Coγ ray. Since the globular embryo stage, the embryo size of ssm1 was significantly smaller than that of LH11. The dry seed weight of ssm1 was only 39.69% of the wild type LH14. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…UDP glycosyltransferases genes play an important role in plant secondary metabolism [32,33]. They can serve as structural genes in the final step of anthocyanin biosynthesis, significantly increasing plant anthocyanin content by inhibiting the feedback of jasmonate signaling [34], as well as participating in plant detoxification processes via interactions with transcription factors [35,36]. This study found that UDP glycosyltransferase and its related gene cluster played an important role in resisting the stress caused by F. oxysporum infection in peanut plants.…”
Section: Discussionmentioning
confidence: 96%
“…UDP glycosyltransferases genes play an important role in plant secondary metabolism [32,33]. They can serve as structural genes in the final step of anthocyanin biosynthesis, significantly increasing plant anthocyanin content by inhibiting the feedback of jasmonate signaling [34], as well as participating in plant detoxification processes via interactions with transcription factors [35,36]. This study found that UDP glycosyltransferase and its related gene cluster played an important role in resisting the stress caused by F. oxysporum infection in peanut plants.…”
Section: Discussionmentioning
confidence: 96%
“…RNA-seq data from cultivated peanuts and wild Arachis monticola identified genes uniquely expressed during seed development, with certain proteins potentially linked to increased seed size in cultivated varieties (Li et al, 2021b). Differences in gene expression between genotypes with varying seed size and oil content have identified pathways related to plant hormones and fatty acid biosynthesis as critical for seed related traits (Guo et al, 2022).…”
Section: The Trait-related Regulation Of Peanut Seed Development Base...mentioning
confidence: 99%
“…Until now, very little was known about the regulation mechanism of peanut seed size. In their study, Guo et al [8] used transcriptomic methods to understand the molecular mechanism of peanut seed size and identify the key gene that controls peanut yield and quality. They identified a small seed mutant1 (ssm1) by irradiating peanut cultivar Luhua11 (LH11) using a 60 Coγ ray.…”
mentioning
confidence: 99%